A comparative study of radiofrequency micro-needling with platelet rich plasma and fractional LASER in acne scar management - Hoq, Abu Jafar M. Shahidul; Alam, M. Shah; Rahman, G. M. Matiur (International Journal of Research in Dermatology, 2022)
Background: Acne scars (AS) results in permanent scarring causes facial disfigurement to the patients. The aim of the study was to assess the comparative effectiveness and outcomes of radiofrequency micro needling and fractional carbon dioxide laser methods in treating acne scars. Methods: This comparative observational study was conducted in the Ibn Sina diagnostic and consultancy center, Dhaka, Bangladesh during the period from January 2019 to December 2020. In total 30 patients with acne scar were selected as the study population. Among total participants, 15 patients who underwent radiofrequency micro needling treatment method were denoted as group-1 and the rest 15 patients who underwent carbon dioxide laser treatment method were denoted as group-2 patients. All data were processed, analyzed and disseminated by Microsoft (MS) office and statistical package for the social sciences (SPSS) version 26. Results: In this study, in group A as per Goodman and Baron scale at the baseline 40% had grade-3 and 60% had grade-4 status. In the same group, after treatment 23.33, 30.00%, 20.00% and 13.33% patients improved up to grade 1, grade 2, grade 3 and grade 4 status respectively. On the other hand, in group-2, after treatment 26.67%, 50.00%, 20.00% and 13.33% patients improved up to grade 1, grade 2, grade 3 and grade 4 status respectively. Finally, according to the mean Goodman and Baron scale scores in both the groups, we found extremely significant correlations between both the baseline and after treatment status where <0001. Conclusions: Both radiofrequency micro needling and fractional CO2 laser treatment methods are effective for the treatment of acne scars.